Successful factors determining the significant relationship between e-governance system and government operational excellence - Almahdy Alhaj Saleh; Imad Fakhri Taha Alyaseen (Bulletin of Electrical Engineering and Informatics, 2021)
Every government's major objective is to provide the greatest services in order to establish efficiency and quality of performance. Syria's government has understood how critical it is to go in the direction of information technology. However, there are gaps and poor links across government sectors, which has tainted the image of Syrian e-governance. As a result, one of the main aims of this study is to figure out what factors impact Syrians' acceptance of the e-government system. A total of 600 questionnaires were delivered to Syrian individuals as part of a survey. The data was analysed using the structural equation model (SEM) using AMOS version 21.0. User intention to utilise an e-government system was shown to be influenced by performance expectations, effort expectations, system flexibility, citizens-centricity, and facilitating conditions. Assurance, responsiveness, reliability, tangibles, and empathy are five fundamental factors that have a major impact on government operation excellence. Behavioural Intention is being utilised as a mediator between the government operation excellence (GOE) initiative and the e-government platform.